Phase Time and Conductance Phenomena in the Tunneling of Uncoupled Holes - Arias-Laso, S.; Diago-Cisneros, L. (Revista Cubana de Física, 2009)
A calculation of the behavior of the conductance through resonant double barrier (n = 2 cells) and superlattice (n > 2 cells), for systems with uncoupled channels is presented. The numerical calculation was done using III and V semiconductors, such as GaAs and AlAs physical systems. Based on the Multicomponent Scattering Approach the twoprobe Landauer conductance and the phase time are calculated and interpreted. An oscillatory behavior of the conductance for a superlattice for uncoupled holes is observed, as we expected. This model provides evidences of the classical Hartman prediction for energies under the barrier height for uncoupled heavy and light holes, while a non linear dependence of the phase time with the barrier width, the Ramsauer – Townsend oscillations, for energies above the barrier is observed.